Paravertebral anaesthesia in goats: a comparative study of various local analgesic agents - Akter, M. A.; Islam, M. N.; Alam, M. M.; Alam, M. R. (International Journal of Scientific Reports, 2025)
Background: Paravertebral nerve block is commonly used as a method of choice for surgical procedures in ruminants. The aims of this study were to compare the effects of different local analgesic agents for paravertebral nerve block. Methods: In this study, fifteen apparently healthy female goats weighing 10-13 kg were allocated into three groups: group A (2% Lidocaine HCl: 4 mg/kg BW), group B (2% lidocaine HCl with epinephrine: 4 mg/kg BW), and group C (0.5% bupivacaine: 1 mg/kg BW). All these local analgesic agents were injected to block the T13, L1 and L2 spinal nerves. Results: Among all groups of animals, group B had the longest period of anesthesia followed by group C and group A. All the animals in groups A, B, and C exhibited a substantial change (p<0.05) in their clinical parameters while receiving local anesthesia. During this study, the value of hemoglobin, packed cell volume, total erythrocyte count, and total leukocyte count were altered significantly (p<0.05) in the animals of group A, B and C at different time intervals after paravertebral administration of different local analgesic regimens. In terms of serum biochemistry, throughout the analgesic period, substantial (p<0.05) alterations were observed in alanine transaminase (ALT), aspartate transaminase (AST), urea, cortisol, and electrolyte level of all experimental groups. Conclusions: Based on the results, it can be inferred that the paravertebral injection of 2% lidocaine with epinephrine results in longest duration of analgesic effect with some undesirable systemic effects on renal and hepatic responses.